Prognosis in pregnant women with systemic lupus erythematosus following pregnancy management. / El pronóstico en las mujeres embarazadas con lupus eritematoso sistémico tras el manejo del embarazo. - Liu, En-Ling; Liu, Zheng; Han, Bao-Feng; Ma, Hong-Xiu; Li, Shuai-Shuai; Zhou, Yu-Xiu (Investigación Clínica, 2020)
Abstract.This study was aimed to understand the effects of pregnancy management in the prognosis for pregnant women with systemic lupus erythematosus (SLE). A total of 217 pregnant patients who were diagnosed with SLE were divided into two groups, the control group (n = 96) and the intervention group (n = 121). The intervention group was treated with routine treatment and nursing care with additional pregnancy management, while the control group was treated with only routine treatment and nursing care. Additionally, 195 normal pregnant women were selected as the healthy controls in the same period. No significant difference of clinical features was observed in the three groups. Compared with the healthy control, increased ANA titer and dsDNA, lower immunoglobulin complement, renal damage, blood system damage, increased SLEDAI score and BILAG score were observed in the control group and the invention group. Both the control group and the intervention group showed significant increases in the incidences of PIH, premature delivery, fetal loss and neonatal complications as well as a significant decrease in neonatal weight compared with the healthy control. SLE activity rate and incidences of PIH, premature delivery and neonatal complications were significantly decreased; while neonatal weight was greatly increased in the intervention group compared with the control group. Low immunoglobulin complement, renal damage, increased dsDNA, and low immunoglobulin complement were independent risk factors for increased SLE activity rate, fetal loss, premature delivery and neonatal complications, respectively. The present study indicates that pregnancy management for pregnant SLE patients could significantly improve maternal and neonatal outcomes.Resumen. Este estudio tuvo como objetivo comprender los efectos del manejo del embarazo en el pronóstico para embarazadas con lupus eritematoso sistémico (SLE). Se estudiaron 217 embarazadas con diagnóstico de SLE divididas en dos grupos, control (n=96) y de intervención (n=121). El grupo de intervención recibió tratamiento de rutina y de enfermería con manejo del embarazo, mientras que el otro grupo solo tratamiento de rutina y de enfermería. Además, 195 embarazadas normales fueron seleccionadas como grupo control sano. Se observó mayor titulación ANA y dsDNA, menor complemento de inmunoglobulinas, daño renal, daño del sistema arterial, aumento de la cuenta de SLEDAI y el índice BILAG en el grupo control y el de intervención, en comparación con el control sano. El grupo control y de intervención mostraron un aumento significativo en la incidencia de preeclampsia, parto prematuro, pérdida fetal y neonatal, y disminución significativa de peso neonatal en comparación con el control sano. La tasa de actividad SLE y la incidencia de preeclampsia, parto prematuro y las complicaciones neonatales se redujeron significativamente, mientras que el peso neonatal aumentó considerablemente en el grupo de intervención, en comparación con el control. Los resultados del análisis de regresión logistica mostraron que el complemento de inmunoglobulina bajo, daño renal, aumento de inmunoglobulinas y complemento bajo dsDNA, fueron factores de riesgo independientes para el aumento de la tasa de actividad de SLE, pérdida fetal, parto prematuro y complicaciones neonatales, respectivamente. El presente estudio sugiere que el manejo del embarazo en pacientes con SLE podría mejorar significativamente los resultados maternos y neonatales.